Treatment approaches for abdominal migration of peritoneal catheter of ventriculoperitoneal shunt - Kaplan, Metin; Ozel, Seyhmuz Kerem; Donmez, Osman; Kazez, Ahmet (Turkish Neurosurgical Soc, 2007)
Migration of peritoneal catheter into the abdominal cavity is rare. We have discussed and presented the treatment options in two cases with accompanying literature. Abdominal migration of peritoneal catheter appears as a result of shunt fracture and disconnection. The complaints on presentation in the abdominal cavity migration of peritoneal catheter are due to shunt dysfunction and peritoneal irritation. The peritoneal catheter with abdominal migration should be removed in cases where abdominal symptoms are present. This procedure may be easily performed laparoscopically with a single mini incision. In some cases, the catheter may cause adhesions to the intra-abdominal organs. Forcefully pulled catheters may result in organ injuries. One should therefore switch to laparotomy in these cases.
Keywords: abdominal migration; peritoneal catheter; VP shunt complication